Lactoferrin: A glycoprotein that plays an active role in human health - Cao, Xiang; Ren, Yang; Lu, Qinyue; Wang, Kun; Wu, Yanni; Wang, YuHao; Zhang, Yihui; Cui, Xiang-shun; Yang, Zhangping; Chen, Zhi (Frontiers in Nutrition, 2023)
Lactoferrin (Lf), existing widely in human and mammalian milk, is a multifunctional glycoprotein with many functions, such as immune regulation, anti-inflammation, antibacterial, antiviral, and antioxidant. These extensive functions largely attribute to its ability to chelate iron and interfere with the cellular receptors of pathogenic microorganisms and their hosts. Moreover, it is non-toxic and has good compatibility with other supplements. Thus, Lf has been widely used in food nutrition, drug carriers, biotechnology, and feed development. Although Lf has been continuously explored and studied, a more comprehensive and systematic compendium is still required. This review presents the recent advances in the structure and physicochemical properties of Lf as well as clinical studies on human diseases, with the aim of providing a reference for further research of Lf and the development of its related functional products.